Karakter Penafsiran Fadil Salih Al-Samarra’i - Ali Hasan Siswanto (Tebuireng: Journal of Islamic Studies and Society, 2021)
This article was written by the author for several reasons. First, many academics are not familiar with the thought of Fadil Salih Al-Samarra’is interpretation, even though he is one of the commentators who live in the contemporary era. Second, The author thinks that the the Fadil Salih Al-Samarra’i method of interpretation is still not widely known by researchers. Therefore, the author examines one of his commentaries, namely ‘ala tariq al-tafsir al-bayani. The focus of this article is to understand the method of interpreting the Qur'an from the perspective of Fadil Salih Al-Samarra’i. To answer this, the author uses a qualitative-descriptive method with library research using the reading of the original interpretation of al-Samarra’i' in his book, namely al-haqiqat al-lughawiyyah, al-haqiqat al-'urfiyyah, al-haqiqat al-syar'iyyah.